(3fcJ GdbGVi CHj GdMSf Ydi Hf eMeO GdeGhQOis - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hHg fSJYjf , ShQI eQje ecjI s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg ef ShQI SHC bhdg (B: (3hGdbhd GdKGfi eG McGg GHf YHGS adeG cGf HYO SfI CcdJ GdCQVI GdYJHI aNQ GdHGH SGbWkG s
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdJaSjQ hYdhe GdbQBfs